As orientações do Banco Mundial para o Brasil: o direito à educação como dever do estado (2016-2022) - Barth, Renata (2024)
This research aimed to analyze the right to education as a duty of the state formulated in the World Bank's specific guidelines for Brazil in the period 2016-2022, understanding the meaning of the right to education for the international organization in the period, as well as comparing these guidelines with the Brazilian legal arrangement (educational law) during the same period. To contextualize the research, the trajectory and evolution of the right to education in Brazil was investigated, addressing how it was influenced by economic and political changes. Next, the right to education formulated in the World Bank's guidelines was examined in the specific documents for Brazil in the 2016-2022 period. Finally, we analyzed the relationship between changes in federal legislation regarding the right to education as a state's duty and the World Bank's guidelines for the same period. The methodological procedure adopted was based on bibliographical and documentary research. The results conclude that the context of the period from 2016 to 2022 is aligned with the regulatory ultra-liberal educational project, whose policies treat education as a service to be provided and not as a right, aimed at conforming to the established social order and further emptying the critical-emancipatory potential of education and the right to education as a duty of the Brazilian state.